2008
DOI: 10.1080/00220380802468579
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and Democracy

Abstract: Most models and empirical tests of the relationship between corruption and democracy assume corruption falls as democracy matures. Yet recent theoretical developments and case evidence suggest an inverted U relationship between the two, although so far no one has tested for this relationship. By drawing on a panel data set covering a large number of countries between 1982-1997, substantial empirical support is found for an inverted U relationship between the durability (age) of democracy and corruption. Fortun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(51 citation statements)
references
References 45 publications
4
46
0
1
Order By: Relevance
“…The results are echoed by Dong and Torgler (2010) and Rock (2009) who concur that corruption is caused by economic hardships; however they do not mention Hunhu/Ubuntu decay of moral values and greed which are surfacing in this study as causes of unethical behaviour by stakeholders in the medical insurance industry. This revelation shows that lack of or decay of Hunhu/Ubuntu can cause declining performance in organizations through pilferage, a major problem in the medical insurance industry in Zimbabwe.…”
Section: Determinants Of Unethical Behaviour By Service Providers; Susupporting
confidence: 49%
See 1 more Smart Citation
“…The results are echoed by Dong and Torgler (2010) and Rock (2009) who concur that corruption is caused by economic hardships; however they do not mention Hunhu/Ubuntu decay of moral values and greed which are surfacing in this study as causes of unethical behaviour by stakeholders in the medical insurance industry. This revelation shows that lack of or decay of Hunhu/Ubuntu can cause declining performance in organizations through pilferage, a major problem in the medical insurance industry in Zimbabwe.…”
Section: Determinants Of Unethical Behaviour By Service Providers; Susupporting
confidence: 49%
“…Drawing from the above results, the respondents were of the view that Hunhu/Ubuntu decay was caused by economic hardships and this was echoed by Dong (2011) andRock (2009). Greediness was also cited as one of the causes of unethical behaviour in individuals.…”
Section: Effects Of Hunhu/ubuntu On Risk Management Effortsmentioning
confidence: 88%
“…This study aims to fill the gap by investigating the effects of democracy and political risks on the stock market performance for a set of emerging markets. Several studies on democracy and political risk (see, e.g., Gleditsch and Hegre (1997); Hegre, Ellingsen, Gates, and Gleditsch (2001); Reynal-Querol (2002a,b); and Rock (2009) and their references) have observed that the semi-democracies are more prone to conflicts, corruption and other political risks than full democracies and autocracies. This reflects that the semi-democracies, unlike full democracies and full autocracies, have not yet established strong institutions that might prevent protests and other anti-government activities, which makes these countries more vulnerable to political instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…This result is neither due to skyscrapers being more popular in particular countries (e.g., China or Kuwait) that happen to be autocratic, nor to skyscrapers being 1 Several cross-national measures of political and administrative corruption exists, and have been used to asses links with democracy (e.g., Rock 2009). However most measures rely on perceptions of corruption, which may be artificially inflated in democratic countries with a free press and higher transparency, thus generating biased estimates (see, e.g., Knutsen 2010).…”
Section: Introductionmentioning
confidence: 99%